Health service use, costs, and adverse events associated with potentially inappropriate medication in old age in Germany: retrospective matched cohort study - Heider, Dirk; Meid, Andreas; Quinzler, Renate; Haefeli, Walter E. (Drugs & aging, 2017)
Background Drug-related problems are an important healthcare safety concern in the growing population of older people. Prescription of potentially inappropriate medication (PIM) is one aspect of this...